Smartphone addiction and its associated behaviors among medical and dental students in Pakistan: A cross-sectional survey - Sufiyan Kamal; Shaheera Kamal; Syed Muhammad Mubeen; Aresha Masood Shah; Syeda Sana Samar; Rida Zehra; Haya Khalid; Ramsha Naeem (Wolters Kluwer Medknow Publications, 2022)
INTRODUCTION: Addiction refers to the irresistible urge to engage in certain actions or dependence on a particular substance despite knowing negative consequences. The current study evaluated the severity of Smartphone addiction and the factors associated with cell phone-like activity. Materials and Methods: This cross-sectional study was conducted from July to August 2019 among medical and dental students in Karachi, Pakistan. A pretested self-administered questionnaire was used among 400 students. The mobile phone addiction was assessed using a 20-item, Mobile Phone Addiction Scale. A two-stage cluster analysis was used to assess mobile phone addiction-like behaviours. Chi-square test was used to find associations between categorical variables. Kolmogorov-Smirnov to test normality of data were also used. A P < 0.05 was considered to be statistically significant for all tests. RESULTS: Out of the total 400 students, the majority 316 (79%) comprise female students. The mean age was 20.54 ± 1.59 years. In 184 (48%) students, there was evidence of mobile phone addiction-like behavior. The prevalence was higher in female than male students and among older compared to adolescent students; the differences were statistically nonsignificant. A higher median score ≥ of 4 is found in questions related to components reflected intense desire, impaired control, and tolerance and harmful mobile use. CONCLUSION: This study highlights that a large number of students are addicted to their smartphones. Smartphone addiction continues to be the most problematic addiction aided by the presence of intense desire, impaired control tolerance, and harmful mobile use. The phenomenon must be fully understood to draw deeper and richer inferences about the origins of this addictive behavior, which is becoming more prevalent in our Pakistani society on a daily basis.